Sex tourism in Brazil: an analysis of EMBRATUR advertising during the military regime - Rozendo, Ana Flavia Moreira Sampaio; Rozendo, Adriano da Silva [UNESP] (Univ Federal Fluminense, Inst Ciencias Sociedade & Desenvolvimento Regional, 2024)
During military regime, the Brazilian Tourism Company (EMBRATUR), was created. Part of its strategy of marketing for foreign countries began to focus on the image of women's bodies. The literature points that EMBRATUR's advertising in the 1970s and 1980s was responsible for making Brazil a destination for international sexual tourism. Twenty-nine advertisements from that period were located and transcript by a visual content description process. The material was submitted IRaMuTeQ analysis, which grouped the content into general tourism categories and specific categories related to the female body, giving rise to two classes: tourism and woman. It was observed evidences that advertising has contributed to the construction of Social Representations and negative attitudes about Brazil abroad, related to sexual tourism.
Keywords: Tourism; sexual; Brazil